An Office-Based Fluid to Fluid Exchange Technique for the Treatment of Postvitrectomy Vitreous Cavity Hemorrhage and Secondary Glaucoma - Sergio E. Hernandez-Da Mota (Case Reports in Ophthalmological Medicine)
A case of postvitrectomy hemorrhage with secondary glaucoma successfully treated with an office-based fluid to fluid exchange is described. A 25 Ga trocar was placed 3 mm from the sclerocorneal limbus at the 2 o’clock position and connected to a 250 cc elevated bottle of balanced salt solution (BSS) through an intravenous (IV) line and an infusion cannula. Afterward, a 25 Ga needle was inserted 3 mm from the limbus at the 5 o’clock position approximately. The BSS fluid entered the eye through the 25 Ga trocar lavaging the vitreous cavity and the anterior chamber. About 4 to 6 cc of hemorrhagic fluid egressed the eye through the 25 Ga needle.